2014
DOI: 10.1002/chem.201403991
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Micelle Synthesis of Colloidal Nickel–Manganese Layered Double Hydroxide Nanosheets and Their Pseudocapacitive Properties

Abstract: Colloidal nanosheets of nickel-manganese layered double hydroxides (LDHs) have been synthesized in high yields through a facile reverse micelle method with xylene as an oil phase and oleylamine as a surfactant. Electron microscopy studies of the product revealed the formation of colloidal nanoplatelets with sizes of 50-150 nm, and X-ray diffraction, energy dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy studies showed that the Ni-Mn LDH nanosheets had a hydrotalcite-like structure with a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Besides, in Figure b, the typical diffraction peaks of a hydrotalcite‐like structure can be observed clearly at 11.34°, 22.74°, 34.41° in LDH and LDH/PC‐1. These peaks are properly agreed to previous literatures on NiMn‐LDH and can be ascribed to (003), (006), and (012) planes, respectively, investigating a successful synthesis of NiMn‐LDH. Nevertheless, the diffraction peaks of PC cannot be found clearly in the XRD pattern of LDH/PC, probably because much too weak to be detected.…”
Section: Resultssupporting
confidence: 91%
“…Besides, in Figure b, the typical diffraction peaks of a hydrotalcite‐like structure can be observed clearly at 11.34°, 22.74°, 34.41° in LDH and LDH/PC‐1. These peaks are properly agreed to previous literatures on NiMn‐LDH and can be ascribed to (003), (006), and (012) planes, respectively, investigating a successful synthesis of NiMn‐LDH. Nevertheless, the diffraction peaks of PC cannot be found clearly in the XRD pattern of LDH/PC, probably because much too weak to be detected.…”
Section: Resultssupporting
confidence: 91%
“…The resultant ultrathin Mg 2+ -Al 3+ LDH platelets had a uniform height of around 1.5 nm and a diameter of about 40 nm. This work clearly confirms that the physically confined effect of a 30 It is noted that the mechanism, i.e. Very recently, B. Lim et al reported that Cl Àintercalated ultrathin Ni 2+ -Mn 3+ LDHs could be synthesized in high yield through a facile reverse micelle method with xylene as an oil phase and oleylamine as a surfactant.…”
Section: Bottom-up Methods: One-pot Precipitationsupporting
confidence: 83%
“…In 2006, D. O'Hare et al firstly reported a facile one-step synthesis of Mg 2+ -Al 3+ LDH monolayers in a reverse microemulsion. 30 As shown in Fig. These droplets acted as nano-reactors, which provided limited space and nutrients for the growth of LDHs.…”
Section: Bottom-up Methods: One-pot Precipitationmentioning
confidence: 99%
“…With a facile reverse micelle assembly comprising xylene as oil and oleylamine as surfactant, Sim et al successfully produced Ni-Mn layered double hydroxides. 248 …”
Section: Microemulsion Templatesmentioning
confidence: 99%